Complex coacervation of food grade antimicrobial lauric arginate with lambda carrageenan - Trivikram Nallamilli (Current Research in Food Science, 2021)
In this study, the complex coacervation mechanism of Lauric arginate ester (LAE) with λ-carrageenan was studied using turbidimetry, light scattering and electrophoresis. The complexes formed were found to have a bilayer-like structure using small angle X-ray scattering (SAXS) and cryo-TEM (transmission electron microscopy). It was observed that mixing LAE with Sodium dodecyl sulfate (SDS) could significantly reduce the interactions between mixed micelles and λ-carrageenan. The interactions between LAE/SDS and λ-carrageenan were found to be predominantly entropy driven. Mixed micelles of LAE/Tween 20 and LAE/SDS showed significantly less interactions with carrageenan compared to pure LAE micelles. Interfacial properties of complexes were measured using surface tension measurements. It was observed that pure LAE showed good foaming behavior and when mixed with increasing amounts of carrageenan the foaming capacity decreased. Reduction in foam volume was due to reduced availability of free LAE molecules for foam stabilization and due to hydrophilic nature of complexes.